Advantages and Disadvantages of Surface Robots in Various Fields of Application - Kotenko, V. A. (ХНУРЕ, 2025)
The article examines the main advantages and disadvantages of surface robots used in scientific, industrial, civilian, and military domains. The study highlights benefits such as operational safety, cost-effectiveness, autonomy, and design features. It also addresses key limitations, including technical challenges, communication issues, legal regulations, and financial barriers. This analysis provides a comprehensive understanding of the potential and limitations of unmanned surface vehicles as an advanced technological solution.
Keywords: surface robots; water logistics; advantages and disadvantages; scientific research